2018
DOI: 10.1186/s12909-018-1206-2
|View full text |Cite
|
Sign up to set email alerts
|

Remediating lapses in professionalism among undergraduate pre-clinical medical students in an Asian Institution: a multimodal approach

Abstract: BackgroundFostering personal identity formation and professional development among undergraduate medical students is challenging. Based on situated learning, experiential learning and role-modelling frameworks, a six-week course was developed to remediate lapses in professionalism among undergraduate medical students. This study aims to explore the students’ perceptions of their personal identity formation and professional development following completion of the course.MethodsThis qualitative study, adopting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
(71 reference statements)
1
17
0
Order By: Relevance
“…Some interventions used a coaching model in which participants undergoing remediation were supported by a coach throughout the process. Reflection was an important activity of many of the interventions …”
Section: Resultsmentioning
confidence: 99%
“…Some interventions used a coaching model in which participants undergoing remediation were supported by a coach throughout the process. Reflection was an important activity of many of the interventions …”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the literature review, several authors [26,32] have indicated that the reflective process can be carried out individually or with external feedback. In this experience, the two groups pointed out the greater importance of reflecting with their peers than with the instructor.…”
Section: Discussionmentioning
confidence: 99%
“…Reflection, therefore, can be defined as engaging in a cognitive process in order to learn from experiences [6,16,23] and can be conducted through individual inquiry or in collaboration with others. Regarding individual reflective learning, instruments such as portfolios [20] or reflective journals [26] are used, where levels of reflection can be evaluated through forms of narrative. In these instruments, the quality of reflection varies according to the learner's ability to ask the relevant questions that will lead to learning [27].…”
Section: Eca (Extracurricular Activities) To Promote Reflective Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…We noted the differences in the requested supports for academic activities between experts and novices in the context of pediatric clinical research. In response to the “generational gap,” clinical research curriculum developers need to consider the antecedents of the gap, including age, clinical experience, and cultural variations (13) , (14) . Recent literature has emphasized that clinical research educators should pay attention to the differences in value systems among different generations of physicians to foster cross-generational relationships and to achieve effective teaching in clinical medicine (15) , (16) .…”
Section: Discussionmentioning
confidence: 99%